REAL TIME POLYMERASE CHAIN REACTION (RT-PCR) FOR DNA PIG CONTAMINATION IDENTIFICATION SAUSAGE IN SIX DISTRICT PANDEGLANG BANTEN: IDENTIFIKASI KONTAMINASI BABI PADA SOSIS DENGAN MENGGUNAKAN REAL TIME POLYMERSE CHAIN REACTION (RT-PCR) DI 6 (ENAM) KECAMATAN KABUPATEN PANDEGLANG BANTEN - Hadi Susilo (Universitas Mathla’ul Anwar Banten, 2021)
Sausage is a meat product processed that is popular food especially in Pandeglang, Banten Province. The importance of halal certificates or the existence of the MUI (Indonesian Ulama Council) halal logo for processed meat products makes Muslim people confident to consume them. The aim this research was to identify pig DNA contamination in sausage products in six districts in Pandeglang without the MUI halal labels using RT-PCR (Real Time-Polymerase Chain Reaction). RT PCR that can calculate to pig to fill these sample free from pig contamination. This research was divided into two stage, the first stage is extracted or carried out DNA and the second stage is RT PCR analysis. The results of the DNA purity test on sausage samples had DNA purity values ​​of 1.84-1.9 (A260 / A280) and resulted in sample concentrations ranging from 37.8 to 102.5 ng / µl. The only amplification on the FAM curve was in the positive control pig. the Cq value ranges from 30 - 31.29. The results of RT PCR on sausage samples in the district area in Pandeglang Banten did not detect the presence of pig DNA.